2020
DOI: 10.1182/bloodadvances.2020003349
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of symptomatic, image-confirmed venous thromboembolism following hospitalization for COVID-19 with 90-day follow-up

Abstract: Although COVID-19 has been reported to be associated with high rates of venous thromboembolism (VTE), the risk of VTE and bleeding after hospitalization for COVID-19 remains unclear, and the optimal hospital VTE prevention strategy is not known. We collected retrospective observational data on thrombosis and bleeding in 303 consecutive adult patients admitted to the hospital for at least 24 hours for COVID-19. Patients presenting with VTE on admission were excluded. Data were collected until 90 days after admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 32 publications
6
73
0
4
Order By: Relevance
“… 4 , 10 , 11 In non-hospitalised patients with COVID-19—ie, those with mild disease—the incidence of venous thromboembolism is unknown. A recent study 12 found a venous thromboembolism incidence of 2·6% in the first 90 days after hospital discharge in patients who did not use anticoagulant therapy or prophylaxis, but another study 13 found a much lower incidence of 4·8 per 1000 discharged patients, which was similar to the incidence shown in patients who were discharged after admission for non-COVID-19 related disease. In addition to venous thromboembolism, increased prevalence of arterial thrombotic events such as myocardial and cerebral infarction (up to 3%, 95% CI 2–5% in an ICU setting) has been reported, 14 and remarkably high numbers of thrombosis in extracorporeal circuits (up to 8%) have been observed.…”
Section: Clinical Features Of Covid-19-associated Coagulopathymentioning
confidence: 75%
“… 4 , 10 , 11 In non-hospitalised patients with COVID-19—ie, those with mild disease—the incidence of venous thromboembolism is unknown. A recent study 12 found a venous thromboembolism incidence of 2·6% in the first 90 days after hospital discharge in patients who did not use anticoagulant therapy or prophylaxis, but another study 13 found a much lower incidence of 4·8 per 1000 discharged patients, which was similar to the incidence shown in patients who were discharged after admission for non-COVID-19 related disease. In addition to venous thromboembolism, increased prevalence of arterial thrombotic events such as myocardial and cerebral infarction (up to 3%, 95% CI 2–5% in an ICU setting) has been reported, 14 and remarkably high numbers of thrombosis in extracorporeal circuits (up to 8%) have been observed.…”
Section: Clinical Features Of Covid-19-associated Coagulopathymentioning
confidence: 75%
“…Analysis from the first wave reported that COVID-19 ARDS patients developed more thrombotic complications compared to non-COVID-19 ARDS patients [9] . Intensive Care Unit (ICU) admission and the need for mechanical ventilation have been identified as independent risk factors for thrombosis in COVID-19 [10] . Thrombotic events are independently associated with mortality [11] .…”
Section: Methodsmentioning
confidence: 99%
“…The cumulative incidence of thrombosis and hemorrhage at day 30 post discharge were reported to be 2.5% and 3.7% respectively in the USA (Appendix Table 2) [73]. Retrospective studies from the UK have shown a similar rate of venous thromboembolism of approximately 3%, whereas it has been estimated that the odds of such events following a hospital discharge are 60% higher in the post-acute COVID-19 setting compared to 2019 [101,102]. However, even lower rates of deep vein thrombosis (<1%) assessed by venous ultrasound have been reported in other prospective, post-acute COVID-19 studies conducted in Belgium and China, including a low proportion of patients receiving thromboprophylaxis [103,104].…”
Section: Hematopoietic Systemmentioning
confidence: 99%